Po’s Perseverant Journey in Kung Fu Panda Movie - Kusuma Wijaya; Muchammad Daffa Firzatullah; Erlis Hersetya Firda; Rindrah Kartiningsih; Rommel Utungga Pasopati (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
This paper examines the theme of perseverance in the animated film Kung Fu Panda (2008), focusing on the journey of the protagonist, Po, as an embodiment of resilience and determination. The story follows Po, an overweight and unskilled panda, who dreams of becoming a kung fu master. Po is unexpectedly chosen as the Dragon Warrior, tasked with protecting the Valley of Peace. Through hard work, belief in himself, and overcoming self-doubt, Po demonstrates that perseverance, rather than natural talent, is the key to success. The purpose of this study is to analyze how Po’s character arc reflects the importance of perseverance in overcoming adversity and achieving personal growth. The research adopts a narrative analysis approach, focusing on Po’s interactions with other characters throughout the film. This paper explores how Po’s perseverant journey aligns with Albert Bandura’s concept of self-efficacy, where persistence, belief in one’s abilities, and overcoming negative feedback led to eventual success. The analysis reveals that Po’s perseverance is key not only to his success as the Dragon Warrior but also to his self-acceptance and personal fulfilment. The conclusion highlights how the film serves as an inspirational narrative, teaching audiences that persistence and belief in oneself are vital components of achieving greatness, regardless of one’s initial circumstances.